2016
DOI: 10.5539/jms.v6n1p192
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Couples and Marrigeable Singles in Establishing Joint Fashion Business

Abstract: Entrepreneurship has been observed to work among couples who have mutual understanding and trust. It has also been observed to have more advantages in terms of the synergy that can bring about achieving more, one's business been in safe hands and building marital fidelity. Nevertheless, it has also been conceived by some individuals that joint business among couples can lead to instability and arguments that arise from financial matters of the business. There are several studies in marriage and family business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…However, research on copreneurs is still emerging. An advantage of a copreneurial business is the synergy that can result in higher achievements, while arguments and instability that arise from financial matters of the business can be a disadvantage (Amubode et al, 2016;Smith, 2000).…”
Section: Copreneurshipmentioning
confidence: 99%
“…However, research on copreneurs is still emerging. An advantage of a copreneurial business is the synergy that can result in higher achievements, while arguments and instability that arise from financial matters of the business can be a disadvantage (Amubode et al, 2016;Smith, 2000).…”
Section: Copreneurshipmentioning
confidence: 99%
“…Close relationships of a couple may create more difficulties than such intimacy can help overcome (Fitzgerald & Muske, 2002). There are also disadvantages which include conflicts in workplaces which if not well managed may spill over to the home, a downturn in the family business which may lead to financial stress boredom (when couples are together every day) and lack of financial trust (Amubode et al;. Copreneurial structured family businesses report a higher level of tension more than non-copreneurial family business (McDonald, Marshall & Delgado, 2017).…”
Section: The Negative Effect Of Corpreneurial Businessmentioning
confidence: 99%
“…It has been observed that entrepreneurship work among couples who have mutual understanding and trust (Amubode et al; The respondents were asked to rank their level of agreement to statements on perceived success as coupreneurs. Results from the analysis of their responses showed positive means ranging from 4.34 to 4.68, with a standard deviation be tween 0.51 and 0.80.…”
Section: Factors Responsible For Effective Corpreneurial Businessmentioning
confidence: 99%
See 1 more Smart Citation